Space Regainers in Pediatric Dentistry: A Review - Aina Desmarani; Rosada Sintya Dwi; Ulfa Yasmin (Journal of Indonesian Dental Association, 2024)
Early loss of primary teeth can cause various problems, especially the loss of space required for permanent teeth eruption that leads to potential malocclusion. Space regainers are appliances that used to regain the space lost in some cases. There are different designs of space regainers, depending on the patient’s cases, and this article aims to summarize fixed and removable space regainers in pediatric dentistry.